Experimental investigation of unequal-depth-beam-to-column joints with t-shape connector. (1st November 2018) - Mou, Ben; Pang, Liyi; Qiao, Qiyun; Yang, Yiting
Highlights: Seismic behavior of a novel beam-to-column joint was experimentally investigated. The connection consists of unequal depth beams with T-shape connector. . A design method for the T-shape connector was proposed. Abstract: This paper presents the seismic behavior of unequal-depth-beam-to-column joints connected by a T-shape connector. Three specimens are examined under cyclic loading tests. The primary experimental parameters are joints with or without T-shape connectors and beam depth ratio ( Db 2 / Db 1 ) with values of 0.5 and 0.75. The panel zone shear strength of unequal-depth-beam-to-column joints connected by a T-shape connector is 20% higher than that of common unequal-depth-beam-to-column joint under the same conditions. The influence of beam depth ratio on the panel zone shear strength of unequal-depth-beam-to-column joints connected by a T-shape connector is limited. The contribution of the T-shape connector web on the flexure moment of whole beam is less than 3%, indicating that the T-shape connector web does not resist the flexure moment but resists the shear force. Hysteresis curves of the panel zone for unequal-depth-beam-to-column joints connected by T-shape connectors are stable, showing excellent ductility and energy dissipation capacity. The equivalent viscous damping coefficients corresponding to the three specimens range from 0.47 to 0.51 in the ultimate stage. A design method for the T-shape connector is proposed and the calculation formulas are deduced.